Investigating The Asymmetric Effect of Food Commodity Price on The Volatility in Indonesia - Sari, Linda Karlina; Achsani, Noer Azam; Sartono, Bagus; Anggraeni, Lukytawati (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Volatility can be measured, but in fact, there is still frequent debate over the selection of precise measurements in describing volatility. In Indonesia, the commodity market is known for its volatile prices, which can impact the livelihood of farmers, traders, and the wider economy. The existence of possible asymmetry in the behavior of food commodity price volatility in the Indonesian market is not yet known. This paper aims to determine the best model to describe the volatility and to investigates the presence of the asymmetric effect on the volatility of food prices in Indonesia, over the period 2009-2019, on a monthly basis. Modeling of volatility uses the GARCH family model, both symmetric and asymmetric. The results showed that the GARCH asymmetric model produces better performance than the symmetric GARCH. Through the best GARCH asymmetric model, the food commodities used in this study showed a statistically significant asymmetrical effect on volatility. Nevertheless, policymakers and market players need to be aware of the impact of market volatility and implement measures such as real-time price information systems to mitigate its effects. The government can increase food production by providing support to farmers in managing supply efficiency and improving agricultural infrastructure. Keywords: agricultural commodity, asymmetric effect, asymmetric GARCH, modeling volatility